Algorithm design for wireless networks with minimized overhead costs - Abhik Banerjee (2012)
Wireless network performance is typically affected by overheads arising due to unique challenges of the wireless medium. The broadcast nature of the medium implies that the channel is shared among all nodes, thereby prohibiting simultaneous transmissions from neighbouring nodes. This results in contention and collision overheads which get compounded with the increase in the number of nodes, posing great challenges to network scalability. In a multihop scenario, overheads are incurred due to challenges associated with traditional distributed systems. This is aggravated by contention overheads described earlier which make it difficult to disseminate information on a large scale.